1998
DOI: 10.1176/ajp.155.1.124
|View full text |Cite
|
Sign up to set email alerts
|

Functional Magnetic Resonance Imaging of Human Brain Activation During Cue-Induced Cocaine Craving

Abstract: These results suggest that functional MRI may be a useful tool to study the neurobiological basis of cue-induced craving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

34
290
4
7

Year Published

2001
2001
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 400 publications
(336 citation statements)
references
References 8 publications
34
290
4
7
Order By: Relevance
“…These include various portions of the cingulate gyrus (Breiter et al, 1997;Childress et al, 1999;Garavan et al, 2000;Grant et al, 1996;Kilts et al, 2001;Mass et al, 1998;Wexler et al, 2001;Brody et al, 2002), the orbital cortex (Grant et al, 1996;Mass et al, 1998;Wang et al, 1999), the nucleus accumbens (Breiter et al, 1997;George et al, 2001;Kilts et al, 2001), and the insula (Breiter et al, 1997;Wang et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…These include various portions of the cingulate gyrus (Breiter et al, 1997;Childress et al, 1999;Garavan et al, 2000;Grant et al, 1996;Kilts et al, 2001;Mass et al, 1998;Wexler et al, 2001;Brody et al, 2002), the orbital cortex (Grant et al, 1996;Mass et al, 1998;Wang et al, 1999), the nucleus accumbens (Breiter et al, 1997;George et al, 2001;Kilts et al, 2001), and the insula (Breiter et al, 1997;Wang et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these animal models, brain imaging studies in humans have shown that cue-induced cocaine craving is associated with activation of the amygdala and anterior cingulate cortex (Childress et al 1999;Maas et al 1998). The neurochemical substrates underlying such conditioned reinforcement effects are under intense investigation but have been hypothesized to involve glutamatergic afferents from the basolateral amygdala and ventral subiculum as well as dopaminergic projections to the basolateral amygdala and other cortical areas (Berke and Hyman 2000).…”
Section: Brain Stress Systems and Vulnerability To Relapsementioning
confidence: 98%
“…Research suggests that cue-related cocaine craving involves the activation of a network of cortical regions involved in the engagement of attention, and the subsequent ruminations also involve the fronto-parietal network seen in WM rehearsal (Childress et al, 1999;Garavan et al, 2000;Grant et al, 1996;Kilts et al, 2001;Maas et al, 1998). Although speculative, a link between WM demands, cocaine craving and poor error awareness may help explain why cocaine users selfmonitoring, or insight into their own behavior, is particularly poor during craving for the drug (Miller and Gold, 1994).…”
Section: Error Awarenessmentioning
confidence: 99%